Political and Legal Novelty as the Contribution of Indonesian Women’s Movement in the Advocacy on Affirmative Policy in Election and Law on the Abolition of Domestic Violence - Anita Dhewy; Bella Sandiata (Yayasan Jurnal Perempuan, 2019)
This article discusses the novelty of the women’s movement in encouraging women’s political representation and advocating for the elimination of domestic violence. Data is obtained through interviews with actors involved in the women’s movement, especially actors from civil society organizations. The results of the study show that the women’s movement in the Advocacy on Affirmative Policy in Election becomes a sign of the inclusion of women in the political agenda. While the women’s movement in the advocacy for Law on the Abolition of Domestic Violence dismantles private and public dichotomies that are detrimental to women in the contextof domestic violence. This study also shows that women’s movements need strong concepts, adaptive strategies and synergies with various elements to be able to push the women’s agenda and encourage change.